Relationship of chemical structures of textile dyes on the pre-adaptation medium and the potentialities of their biodegradation by Phanerochaete chrysosporium - Martins, M. Adosinda M. (2002)
Azo dye derivatives of azobenzene constitute the largest group of dyes used in the textile industry and possess recalcitrant chemical groups, such as those of azo and sulphonic acid. Some microorganisms are able to degrade these aromatic compounds. In the present work, decolourisation of culture media containing azo dyes by the ligninolytic fungus Phanerochaete chrysosporium was achieved under nitrogenlimited conditions. The dyes used in the study are derivatives of meta- or para-aminosulphonic or aminobenzoic acids and include in their structures groups such as guaiacol or syringol, which are bioaccessible to the lignin degrading fungus P. chrysosporium. The aim of this study was to pre-adapt the microorganism to the structure of the dyes and to establish the relationships of the chemical structure of the dye present in the pre-adaptation medium with the chemical structure of the dye to be degraded. The azo dye used in the pre-adaptation medium that gave the best overall decolourisation performance was a meta-aminosulphonic acid and guaiacol derivative. The azo dye derivative of a meta-aminobenzoic acid and syringol showed a better performance in the decolourisation assays. Preliminary GC-MS studies indicated the formation of a nitroso substituted catechol metabolite, a precursor of aromatic ring cleavage, which was confirmed to occur by an enzymatic assay. The presence of this type of metabolite allows the establishment of a possible metabolic pathway towards mineralisation.